Associations between dynapenia, cardiovascular hospitalizations, and all‐cause mortality among patients on haemodialysis. Issue 5 (2nd August 2022) - Yoshikoshi, Shun; Yamamoto, Shohei; Suzuki, Yuta; Imamura, Keigo; Harada, Manae; Osada, Shiwori; Kamiya, Kentaro; Matsunaga, Atsuhiko
Abstract: Background: Low muscle strength is associated with adverse clinical outcomes in patients undergoing haemodialysis (HD). No studies have reported the association between dynapenia, defined by both low handgrip strength (HGS) and quadriceps isometric strength (QIS), and long‐term clinical outcomes in patients on HD. We examined the associations between dynapenia, cardiovascular (CV) hospitalizations, and all‐cause mortality in the HD population. Methods: This retrospective study used data from outpatients undergoing HD at two dialysis facilities between October 2002 and March 2020. We defined low muscle strength as an HGS of <28 kg for men and <18 kg for women and a QIS of <40% dry weight. Furthermore, we categorized dynapenia into three groups: robust ('high HGS and high QIS'), either low HGS or low QIS ('low HGS only' or 'low QIS only'), and dynapenia ('low HGS and low QIS'). The outcomes were all‐cause mortality and a composite of CV hospitalizations and mortality. Cox proportional hazards and negative binomial models were used to examine these associations. Results: A total of 616 patients (mean age, 65.4 ± 12.2 years; men, 61%) were included in the analyses. During the follow‐up (median, 3.0 years), a total of 163 deaths and 288 CV hospitalizations occurred. Patients with the either low HGS or low QIS [hazard ratio (HR), 1.75; 95% confidence intervals (CIs), 1.46–2.10] and dynapenia (HR, 2.80; 95% CIs, 2.49–3.14) had a higher risk of mortality than those in the robust group. When compared with the robust group, the either low HGS or low QIS [incidence rate ratio (IRR): 1.41, 95% CI: 1.00–1.99] and dynapenia (IRR: 2.04, 95% CI: 1.44–2.89) groups were associated with a significantly higher incident risk of CV hospitalizations. Conclusions: Dynapenia (muscle weakness in both upper and lower extremities) was associated with increased risks of all‐cause mortality and CV hospitalizations among patients on HD. Screening for dynapenia using both HGS and QIS may be useful for prognostic stratification in the HD population.